Evaluation of Potassium Levels Before Hemodialysis Access Procedures. Issue 1 (19th May 2014) - Ross, Jamie; DeatherageHand, Deborah
Abstract Few prospective studies have looked at the incidence of hyperkalemia in outpatient hemodialysis access procedures. Our study prospectively evaluated 167 procedures using a preadmit venous blood gas (VBG) and found that 14.3% had moderate or severe hyperkalemia. When the individual procedures were analyzed it was found that 38% of malfunctioning tunneled dialysis catheter (TDC) patients, 20% of new start TDC patients, 22% of thrombectomy patients, and only 5.8% of the angioplasty patients had moderate or severe hyperkalemia. We have changed our practice and now monitor the preprocedure potassium in all but the routine angioplasty patients and treat with the protocol described in the body of the article.